Combating inequality: Rethinking governments role - Blanchard, olivier; Rodrik, Dani (London The MIT press, 2021)
The contributors express widespread agreement that we need to aim policies at economic inequality itself; deregulation and economic stimulus will not do the job. No longer does anyone ask, in relation to expanded social programs, (3z(BCan we pay for it?(3y (BAnd most believe that US taxes will have to rise$1 (Balthough they debate whether the progressivity should focus on the revenue side or the expenditure side, through broad-based taxes like the VAT or through a wealth tax aimed at the very top of the income scale. They also consider the philosophical aspects of inequality$1 (Bwhether it is bad in itself or because of its consequences; the risks and benefits of more radical interventions to change the nature of production and trade; and future policy directions.s
Keywords: Business and economics; Political economy; Labor studies